Use of Brain Stimulation to Improve Swallowing in a Brainstem Stroke Patient with Cricopharyngeal Spasm: Case Report - Sanghavi, Tanvi (Nepalese Medical Journal, 2022)
In India, post-stroke dysphagia affects between 37 and 78 percent of people. In recent years, research into transcranial magnetic stimulation has enhanced our understanding of the neurological aspects of swallowing, thanks in great part to Hamdy and colleagues' pioneering work. TMS has been shown to help with depressive symptoms, anxiety, and parkinsonian symptoms, however, there is no study on how it can help with swallowing. This case study looked at the effects of transcranial magnetic stimulation and transcranial direct current stimulation in combination with standard swallowing training on swallowing function in brainstem stroke patients with cricopharyngeal spasms.